Budesonide/Formoterol Maintenance and Reliever Therapy versus Free-Combination Therapy for Asthma: A Real-Life Study - Kardos, P. (Pneumologie, 2013)
Background: This non-interventional real-life study (NCT00884689) compared budesonide/formoterol (Symbicort®) maintenance and reliever therapy (SMART™) with a free combination of inhaled corticosteroid (ICS) + long-acting β2-agonist (LABA) (in separate inhalers) and as-needed short-acting β2-agonist (SABA) in adult asthma patients with an exacerbation in the past 24 months.Methods: Asthma patients received SMART™ or free-combination ICS + LABA and as-needed SABA for 6 months. Allocation of patients and doses prescribed were at physician’s discretion. No other restrictions applied. Primary endpoint: mean no. of rescue medication puffs/day. Results: 482 patients were included (SMART™ n = 310; free combination n = 172). SMART™ patients used less rescue medication vs the free-combination group (mean difference – 0.27 puffs/day; p = 0.013). Severe asthma exacerbations were rare (mean rate 0.20 vs 0.17/year for SMART™ vs free combination). The mean ICS dose was 615 µg in SMART™ and 678 µg in free-combination group.Conclusions: In this real-life setting, SMART™-treated patients used less rescue medication despite a lower ICS burden vs conventional asthma management with three different inhalers.